Quality of life following total mastectomy with and without reconstruction versus breast-conserving surgery for breast cancer: A case-controlled cohort study. Issue 9 (September 2016) - Howes, Benjamin H.L.; Watson, David I.; Xu, Chris; Fosh, Beverley; Canepa, Maximiliano; Dean, Nicola R.
Summary: Background: Patient-reported outcomes and quality of life following mastectomy are not well understood. This study evaluates the quality of life following surgery for breast cancer and compares outcomes following breast-conserving surgery versus total mastectomy with or without reconstruction. Methods: A case-controlled cross-sectional study was conducted using the validated BREAST-Q™ questionnaire and a study-specific questionnaire to determine patient's views about surgical outcomes. Questionnaires were completed by patients following breast-conserving surgery and total mastectomy with or without reconstruction and by controls without breast cancer. A one-way ANOVA was used to compare mean BREAST-Q™ scores between groups and post hoc analysis using Tukey's and Kruskal–Wallis tests. Results: BREAST-Q™ questionnaires were completed by 400 women (123 controls, 97 breast conservations, 93 mastectomies without reconstruction, 87 mastectomies with reconstruction). Women who had undergone mastectomy and reconstruction had higher scores in satisfaction with breast and sexual well-being domains compared with women who had breast-conserving surgery, and women who had total mastectomy without reconstruction had the lowest scores in these two domains. There was no difference in psychosocial well-being between the groups. Women who had undergone breast-conserving surgery scored the lowest in the physical well-being chest domain and the majority reported breast asymmetry. Conclusion: Our study suggests that women who undergo total mastectomy and breast reconstruction for cancer achieve a quality-of-life outcome that is at least as good as that following breast-conserving surgery. Furthermore, breast conservation has been found to be associated with lower physical well-being (i.e., more pain and discomfort) in the chest area and poorer sexual well-being outcomes.